Penerapan metode nested query untuk menetukan siswa penerima bantuan PIP - Adiat Pariddudin; Muhamad Firdaus (Sekolah Tinggi Ilmu Komputer Binaniaga, 2019)
Cijujung 04 State Elementary School is one of the basic educational institutions that is always developing with the number of students increasing from time to time. Cijujung 04 Public Elementary School is a state school, this school is located in the Cikupa-Nagrak village of Cijujung village, cibungbulang sub-district, Bogor Regency. Public elementary schools or other private elementary schools also have very important data. One of them is a master book. The student handbook is a data set of students studying at the school. Student Parent Book is one of the most important parts of the management of this institution. The notes in the master book must be complete. Includes, student biodata, student grades, and student achievement results from the first semester to graduate school. However, in its implementation so far it has been ineffective and inefficient because it is carried out manually, namely by writing data in a thick ledger or a master book. The teacher also had difficulty finding student data in the parent book and also sought students for prospective recipients of PIP assistance. A system is needed that can be used by teachers to find student data in the parent book and also look for students for potential recipients of PIP assistance. Nested queries or queries are queries that have other queries in them. By using the nested query method in the parent book system, the search process for prospective PIP recipient students can be searched as needed because in the parent book system has a student search feature based on the desired category. Based on the nested query method. From the results of the distribution of questionnaires to test the system distributed to informatics engineering system respondents obtained a percentage of system eligibility of 87% so that it can be categorized as very feasible, while the results of distributing questionnaires to user respondents obtained a percentage of system feasibility of 94.5% so that it can be categorized as very feasible